FROM TRADITIONAL TO MODERN LEADERSHIP IN SECONDARY SCHOOLS: A SYSTEMATIC LITERATURE REVIEW - Desmalini; Salsabila Indah Suciani; Maayang Fa'uni; Mahdum; Jimmi Copriady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Leadership plays a crucial role in determining the effectiveness and quality of education in secondary schools. In recent years, educational leadership has experienced a significant shift from traditional leadership approaches characterized by hierarchical authority and centralized decision-making toward modern leadership models that emphasize collaboration, innovation, and organizational transformation. This study aims to examine the evolution of leadership from traditional to transformational approaches in secondary schools, identify the factors that facilitate or hinder this transition, and explore its implications for school effectiveness, teacher performance, and educational innovation. This study uses a Systematic Literature Review design with a PRISMA approach to analyze 10 articles obtained through the Scopus, ScienceDirect and Google Scholar databases. The findings include five main themes: (1) Impact on School Effectiveness; (2) Drivers of Leadership Transformation; (3) Evolution of Leadership Models; (4) Transformational Leadership Practices; and (5) Future Leadership Trends. The study shows that effective leadership in secondary schools requires a balanced integration of traditional leadership strengths and modern transformational practices to address the challenges of contemporary education. These findings provide valuable insights for educational institutions, educators, and researchers seeking to enhance leadership effectiveness in secondary schools. Keywords: Traditional Leadership; Modern Leadership; Secondary Schools; Systematic Literature Review.